2020
DOI: 10.3389/fnins.2020.00677
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Amygdala in Self-Conscious Emotions in a Patient With Acquired Bilateral Damage

Abstract: Shame plays a fundamental role in the regulation of our social behavior. One intriguing question is whether amygdala might play a role in processing this emotion. In the present single-case study, we tested a patient with acquired damage of bilateral amygdalae and surrounding areas as well as healthy controls on shame processing and other social cognitive tasks. Results revealed that the patient’s subjective experience of shame, but not of guilt, was more reduced than in controls, only when social standards we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…20 The amygdala contributes to the emotional and social behavioural processes. 21 It has been reported that patients with amygdala damage are impaired in recognizing facial expressions of negative emotions. 22 Functional MRI has shown that the amygdala responds differentially to fearful versus happy facial expressions, depending on attentional processes.…”
Section: Discussionmentioning
confidence: 99%
“…20 The amygdala contributes to the emotional and social behavioural processes. 21 It has been reported that patients with amygdala damage are impaired in recognizing facial expressions of negative emotions. 22 Functional MRI has shown that the amygdala responds differentially to fearful versus happy facial expressions, depending on attentional processes.…”
Section: Discussionmentioning
confidence: 99%
“…Moral emotions are crucial in regulating social interactions, as they promote the welfare of the society or of other people (Haidt et al, 2003). Indeed, they provide the emotional drive to properly behave in social interactions (Kroll and Egan, 2004;Piretti et al, 2020;Grecucci et al, 2021), forcing individuals to implement strategies that are optimal over a long period, even though they do not appear functional in the short period (Ridley, 1996;Sober and Wilson, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous neuroimaging studies have explored BPD features in recent years, leading to the identification of some cerebral structural and functional alterations associated with the pathogenesis of BPD. Up to 2013, the majority of studies indicated that structural differences in the amygdala hub, hippocampus and cingulate cortex are involved in affective deficits ( Minzenberg et al, 2008 ; Nunes et al, 2009 ; Ruocco et al, 2012 ; Piretti et al, 2020 ). More recently, alterations in frontal (e.g., orbifrontal cortex, medial prefrontal cortex; Aguilar-Ortiz et al, 2018 ), cortical and subcortical regions ( Ruocco et al, 2016 ; Stanley et al, 2018 ; Davies et al, 2020 ; Lapomarda et al, 2021a , b ) have also been identified.…”
Section: Introductionmentioning
confidence: 99%